Screening of Antioxidant, Antibacterial, Anti-Adipogenic, and Anti-Inflammatory Activities of Five Selected Medicinal Plants of Nepal - Lamichhane G; Sharma G; Sapkota B; Adhikari M; Ghimire S; Poudel P; Jung HJ (Dove Medical Press, 2023)
Gopal Lamichhane,1,2,* Grinsun Sharma,1,3,* Biswash Sapkota,1,4,* Mahendra Adhikari,1,5,* Sandhaya Ghimire,1,* Prakash Poudel,1,6 Hyun-Ju Jung2 1School of Health and Allied Sciences, Faculty of Health Sciences, Pokhara University, Pokhara, 33700, Nepal; 2Department of Oriental Pharmacy and Wonkwang-Oriental Medicines Research Institute, Wonkwang University, Iksan, Jeollabuk-do, 570-749, South Korea; 3Institute of Pharmaceutical Research and Development, College of Pharmacy, Wonkwang University, Iksan, 570-749, South Korea; 4Department of Pharmacy and Clinical Pharmacology, Madan Bhandari Academy of Health Sciences, Hetauda, 44107, Nepal; 5Department of Pharmacy, Institute of Pharmaceutics and Biopharmaceutics, Heinrich Heine University Düsseldorf, Düsseldorf, 40225, Germany; 6Pharmacy Program, Gandaki University, Pokhara, 33700, Nepal*These authors contributed equally to this workCorrespondence: Prakash Poudel; Hyun Ju Jung, Email poudelprakesh@gmail.com; hyun104@wku.ac.krIntroduction: Herbal products have been widely used for the treatment of diseases throughout the ages. In this research, we investigated antioxidant, antibacterial, anti-adipogenic, and anti-inflammatory activities of methanolic extracts of five ethnomedicinally important plants; namely, Alnus nepalensis, Dryopteris sparsa, Artocarpus lacucha, Litsea monopetala, and Lyonia ovalifolia.Methods: We investigated the DPPH free radical scavenging potential, sensitivity of selected bacterial strains towards the extracts using a disc diffusion assay, anti-inflammatory activity in RAW-264.7 cells, and anti-adipogenic activity by the ORO assay in 3T3-L1 preadipocytes.Results and discussion: The extract of A. nepalensis showed significant antioxidant activity (IC50=4.838 μg/mL), followed by A. lacucha, L. monopetala, and L. ovalifolia, exhibiting comparable IC50 values to that of ascorbic acid (IC50=5.063 μg/mL). Alnus nepalensis also showed good antibacterial activity in disc diffusion methods, with remarkable zones of inhibition in A. baumannii (14.66 mm) and P. mirabilis (15.50 mm) bacterial species. In addition, A. nepalensis was found to increase adipogenesis in 3T3-L1 cells, evidenced by increased lipid deposition in differentiated 3T3-L1 cells. A similar pattern of increased adipogenesis was observed on treatment with L. ovalifolia extracts. On the other hand, A. lacucha effectively reduced lipid deposition in 3T3-L1 cells at 100 μg/mL (75.18± 6.42%) by inhibiting adipogenesis, showing its potential use in the management of obesity. Furthermore, A. lacucha 100 μg/mL (15.91± 0.277 μM) and L. monopetala 75 μg/mL (12.52± 0.05 μM) and 100 μg/mL (11.77± 0.33 μM) significantly inhibited LPS-induced nitric oxide production in RAW 264.7 cells. Also, A. nepalensis and L. ovalifolia inhibited NO production significantly, endorsing their anti-inflammatory potential.Conclusion: The findings from these in-vitro studies suggest that the selected five plants possess remarkable antioxidant, antibacterial, anti-adipogenic, and anti-inflammatory activities. This study opens the door to conduct further advanced in-vivo experiments to find possible lead compounds for the development of valuable therapeutic agents for common health problems.Keywords: Alnus nepalensis, Dryopteris sparsa, Artocarpus lacucha, Litsea monopetala, Lyonia ovalifolia